Effect of encapsulated Tahongai (Kleinhovia hospita l.) leaf extract on growth performance, intestinal condition and antioxidative status of broilers raised in high stocking density pens - Yusuf, R.; Ismadi, V. D. Y. B.; Kismiati, S.; Sugiharto, S. (Diponegoro University, 2024)
The objective of the present study was to investigate the effect of Kleinhovia hospita L. extract (KE) on growth performance, intestinal condition and antioxidative status of broilers raised in high stocking density pens. A total of 370-day-old broiler chicks were randomly grouped into five groups with five replicates. The groups were T0 (chicks raised in normal density, 10 birds/m2; as a negative control), KE0 (chicks raised in high density, 16 birds/m2, without KE supplementation; as a positive control), KE0.25, KE0.5 and KE1 (chicks raised in high density with KE supplementation of 2.5, 5 and 10 g/kg, respectively). Based on the completely randomized design, the data were treated. Results showed that KE1 chicks had the highest (p<0.05) body weight (BW) at day 21 and 28. The T0, KE0 and KE2.5 chicks consumed more (p<0.05) feed than the other treatment groups. The KE0.25, KE0.5 and KE1 showed lower (p<0.05) FCR than the KE0 group. The KE0 chicks showed lower (p<0.05) carcass yield than the other groups. The KE0 had the highest (p<0.05) heart relative weight of all groups. The KE1 had the highest (p<0.05) small intestinal weight, cecum, colon and abdominal fat of any treatment group. Among the groups, crypt depth of the duodenum in KE0 was the lowest (p<0.05). There was no substantial effect of the treatments on the counts of coliform and lactic acid bacteria in the ileum of broilers. The superoxide dismutase (SOD) levels in KE0.5 and KE1 were higher (p<0.05) than those in T0, KE0 and KE0.25 groups. In conclusion, stocking in high density pens negatively af-fected the carcass yield of broiler chickens. Dietary KE supplementation was beneficial in improving FCR and antioxidant status of broiler chickens.